Peace of mind and anxiety in the waking state are related to the affective content of dreams - Sikka Pilleriin; Pesonen Henri; Revonsuo Antti (Springer Nature, 2022)
Waking mental well-being is assumed to be tightly linked to sleep and the affective content of dreams. However, empirical research is scant and has mostly focused on ill-being by studying the dreams of people with psychopathology. We explored the relationship between waking well-being and dream affect by measuring not only symptoms of ill-being but also different types and components of well-being. Importantly, this is the first time peace of mind was investigated as a distinct aspect of well-being in a Western sample and in relation to dream content. Healthy participants completed a well-being questionnaire, followed by a three-week daily dream diary and ratings of dream affect. Multilevel analyses showed that peace of mind was related to positive dream affect, whereas symptoms of anxiety were related to negative dream affect. Moreover, waking measures were better related to affect expressed in dream reports rather than participants’ self-ratings of dream affect. We propose that whereas anxiety may reflect affect dysregulation in waking and dreaming, peace of mind reflects enhanced affect regulation in both states of consciousness. Therefore, dream reports may possibly serve as markers of mental health. Finally, our study shows that peace of mind complements existing conceptualizations and measures of well-being.